2013
DOI: 10.1186/1472-6963-13-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

How managed a market? Modes of commissioning in England and Germany

Abstract: BackgroundIn quasi-markets governance over healthcare providers is mediated by commissioners. Different commissioners apply different combinations of six methods of control ('media of power') for exercising governance: managerial performance, negotiation, discursive control, incentives, competition and juridical control. This paper compares how English and German healthcare commissioners do so.MethodsSystematic comparison of observational national-level case studies in terms of six media of power, using data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…For example, supplier opportunism in the context of Private Finance Initiative contracting in the NHS leads public-sector managers to employ detailed planning practices (Lonsdale and Watson, 2007) and hold private-sector managers accountable to contract specifications (Hebson, Grimshaw and Marchington, 2003), potentially leading to a more difficult situation for profit-making. Moreover, commissioning in English healthcare has traditionally limited competition, since patient choice and cash budgets were both strictly limited (Sheaff et al, 2013).…”
Section: The Conditions Of Profitabilitymentioning
confidence: 99%
“…For example, supplier opportunism in the context of Private Finance Initiative contracting in the NHS leads public-sector managers to employ detailed planning practices (Lonsdale and Watson, 2007) and hold private-sector managers accountable to contract specifications (Hebson, Grimshaw and Marchington, 2003), potentially leading to a more difficult situation for profit-making. Moreover, commissioning in English healthcare has traditionally limited competition, since patient choice and cash budgets were both strictly limited (Sheaff et al, 2013).…”
Section: The Conditions Of Profitabilitymentioning
confidence: 99%
“…With respect to service use, Barnes et al (2013) found that in the context of inappropriate treatment of routine childhood (Baxter et al 2007; PCT case study); characteristics of commissioning managers (Checkland et al 2012; PCT); perceptions of value of priority-setting tools (decision support) for resource allocation (Marks et al 2011;PCTs); commissioning services for long-term conditions (Shaw et al 2013;PCTs); priority setting and rationing in PCTs (Robinson et al 2012; PCT case study); AFR framework to aid decision making (Bravo Vergel and Ferguson 2006;PCT); comparisons across commissioning models in Germany and UK (Sheaff et al 2013; PCT and other); views of CCG versus PCT commissioning (Turner et al 2013;PCT and CCG); are GPs best placed to deliver equity and excellence? Comparing GP commissioning with PCT (Gridley et al 2012; PCT and other); APMS contractual processes ; UK APMS); commissioning dental services through PDSS (Newton et al 2006; PDSS); barriers and enablers to commissioning ; PCT survey); engaging pharmacy in pharmaceutical needs assessment for commissioning pharmacy ; PCT) Quantitative: cluster RCT examining impact of commissioning on smoking cessation and entrance of new market players (McLeod et al 2015;PCTs); PBMA for purchasing (Wilson et al 2007; PCT) Mixed methods: redesigning children's services (Barnes et al 2013; PCT); use of external consultants by NHS commissioners (Naylor and Goodwin 2011; PCT interviews and survey); commissioners viewed HLP scheme as an effective model with which to deliver increased volume, quality and reliability of community health services (Kennington et al 2013; HLP) Fundholding practices (n = 1); PBC (n = 2); CCGs (n = 7) 1 quantitative; 9 qualitative 10 Quantitative: impact on cost containment and service use (Dusheiko et al 2006; fundholding) Qualitative: barriers to PBC (Checkland et al 2009; PBC); PBC as a service redesign tool (Slater and White 2007;PBC); investigating disinvestment practices (Rooshenas et al 2013;CCG); exploring development of CCG CCG); attitudes of GPs to commissioning including level of GP engagement with clinical commissioning and attitudes to incentives an...…”
Section: Evidence Of Impact Of Commissioningmentioning
confidence: 99%
“…Most important, regulations intended to maximise provider diversity and competition for patients removed provider competition as a medium of commissioner power. 267 …”
Section: Juridical Controlsmentioning
confidence: 99%